Pengaruh Keanekaragaman Produk dan Store Atmosphere Terhadap Impulse Buying Konsumen Dengan Kualitas Pelayanan Sebagai Variabel Moderating - Harris Manurung; Ira Yana (JOURNAL FOR BUSINESS AND ENTREPRENEURSHIP, 2019)
This study aims to analyze the effect of product diversity and store atmosphere on consumer impulse buying with service quality. The population used in this study is a sample of consumers of Toko Kharisma, with 179 respondents. In the process of collecting data, this research data is collected using a list of statements / questions or questionnaires distributed in the form of google form. Method of determining the number of eligibility of respondents using the hair method which states that the repondent can be 5 to 10 indicators. The data processing method in this study uses the SmartPLS 3 software which is used to test the hypothesis. The results of this study indicate that product diversity has a negative and insignificant effect on impluse buying, store atmosphere has a negative and insignificant effect on impluse buying, service quality has a positive and significant effect on impluse buying, moderation of service quality is unable to strengthen the effect of product diversity on impluse buying, and moderation of service quality can strengthen and significantly influence the effect of strore atmosphere on impluse buying